2011
DOI: 10.1128/jcm.01285-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microevolution Events in Mycobacterium tuberculosis Strains Involved in Recent Transmission Clusters

Abstract: Under certain circumstances, it is possible to identify clonal variants of Mycobacterium tuberculosis infecting a single patient, probably as a result of subtle genetic rearrangements in part of the bacillary population. We systematically searched for these microevolution events in a different context, namely, recent transmission chains. We studied the clustered cases identified using a population-based universal molecular epidemiology strategy over a 5-year period. Clonal variants of the reference strain defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Concerning this, most IS6110 copies have been located outside the DnaA boxes, and the oriC activity has not been affected (26). In this sense, the insertion of IS6110 in the oriC region could be an evolutionary advantage (7). In our study, we observed that the insertion of IS6110 is located outside the described DnaA boxes; therefore, we can assume that IS6110 does not decrease the activity of the oriC region.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Concerning this, most IS6110 copies have been located outside the DnaA boxes, and the oriC activity has not been affected (26). In this sense, the insertion of IS6110 in the oriC region could be an evolutionary advantage (7). In our study, we observed that the insertion of IS6110 is located outside the described DnaA boxes; therefore, we can assume that IS6110 does not decrease the activity of the oriC region.…”
supporting
confidence: 52%
“…Minor variations in IS6110 fingerprints, spoligotypes, or mycobacterial interspersed repetitive-unit (MIRU)-variable-number tandem-repeat (VNTR) loci reveal microevolution in clonal infections (6,8). These changes could have effects on the molecular structure of the mycobacterial genome and the biology of the bacillus (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal variants of the reference strain defining the cluster were found in 9 (12%) of the 74 clusters identified after the genotyping of 612 M. tuberculosis isolates by IS6110 restriction fragment length polymorphism analysis and mycobacterial interspersed repetitive units-variablenumber tandem repeat typing. Clusters with microevolution events were epidemiologically supported and involved 4 to 9 cases diagnosed over a 1-to 5-year period (Pérez-Lago et al, 2011), another study was to compare polymerase chain reaction (PCR)-based methods--spoligotyping and mycobacterial interspersed repetitive units (MIRU) typing--with the gold-standard IS6110 restriction fragment length polymorphism (RFLP) analysis in 101 isolates of Mycobacterium tuberculosis to determine the genetic diversity of M. tuberculosis clinical isolates from Delhi, North India (Varma-Basil et al 2011) and finally, a study where Forty three isoniazid (INH)-resistant M. tuberculosis isolates were characterized on the basis of the most common INH associated mutations, katG315 and mabA -15C→T, and phenotypic properties (i.e. MIC of INH, resistance associated pattern, and catalase activity).…”
Section: Ribotypingmentioning
confidence: 99%
“…6 The IS6110 is an insertion sequence that belongs to IS3 family. IS6110 commonly used for detection of MTB, 7 epidemiological studies 8 and recent transmission. 9 In IS6110-restriction …”
mentioning
confidence: 99%